2019
DOI: 10.1002/adma.201907036
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Domain Wall Motion in Freestanding Single‐Crystal Complex Oxide Thin Film

Abstract: Ferroelectric domain walls in single-crystal complex oxide thin films are found to be orders of magnitude slower when the interfacial bonds with the heteroepitaxial substrate are broken to create a freestanding film. This drastic change in domain wall kinetics does not originate from the alteration of epitaxial strain; rather, it is correlated with the structural ripples at mesoscopic length scale and associated flexoelectric effects induced in the freestanding films. In contrast, the effects of the bondbreaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
(35 reference statements)
0
34
0
1
Order By: Relevance
“…[46] Structural inhomogeneities emerging in unclamped membranes, however, can mask the impact of the substrate release on the switching kinetics. [47] Therefore, preserving high crystal quality in the ferroelectric membranes after the release is important to identify intrinsic changes in switching mechanisms and domain-wall mobilities with the aim of lowering switching times, as is sought after for ultra-high-speed, non-volatile memories, [48] memristors, [49] and neuromorphic networks. [50] Here, we demonstrate that high-quality nanoscale epitaxial films of the ferroelectric Ba 1-x Sr x TiO 3 can be transferred from single-crystal oxide substrates to silicon and polymer substrates without structural degradation.…”
mentioning
confidence: 99%
“…[46] Structural inhomogeneities emerging in unclamped membranes, however, can mask the impact of the substrate release on the switching kinetics. [47] Therefore, preserving high crystal quality in the ferroelectric membranes after the release is important to identify intrinsic changes in switching mechanisms and domain-wall mobilities with the aim of lowering switching times, as is sought after for ultra-high-speed, non-volatile memories, [48] memristors, [49] and neuromorphic networks. [50] Here, we demonstrate that high-quality nanoscale epitaxial films of the ferroelectric Ba 1-x Sr x TiO 3 can be transferred from single-crystal oxide substrates to silicon and polymer substrates without structural degradation.…”
mentioning
confidence: 99%
“…For example, it has been found that in the freestanding state PbZr x Ti 1‐x O 3 and BiFeO 3 thin films attain superelasticity, [ 19 ] sustain extreme strain without being fractured, [ 20 ] deviate from the flat phase of atomic planes and create structural ripples. [ 21,22 ] However, properties of freestanding heterostructures have remained largely unknown. Two intriguing questions in this regard are: First, how does the freestanding state affect the energy landscape of low dimensional ferroelectrics?…”
Section: Introductionmentioning
confidence: 99%
“…Then the film is lifted off from the substrate by etching, laser lift‐off, or a sacrificial layer. [ 14–19 ] Particularly, a lift‐off and transfer technique utilizing a water‐soluble oxide Sr 3 Al 2 O 6 (SAO) as a sacrificial layer is applicable to various perovskite‐based oxides [ 20–26 ] because SAO has a matched lattice constant. For example, a /4 of SAO with a cubic structure (3.964 Å) is close to a of SrTiO 3 (STO) (3.905 Å).…”
Section: Introductionmentioning
confidence: 99%